Development of a predictive model for kerf taper angle in AWJM of Kevlar epoxy composite. (2020) - Kumar, Puneet; Kant, Ravi
Abstract: This paper describes the research work involved in studying the influence of process parameters on kerf taper and development of predicative model for the response in abrasive water jet machining (AWJM) of Kevlar epoxy composite. Four process parameters namely water pressure, stand-off distance, traverse speed and abrasive mass flow rate are considered. To investigate the influence of process parameters on kerf taper, experiments are designed using response surface methodology. Experiments are conducted on flying arm AWJM setup. Kerf taper of machined work pieces is measured using vision measurement system. It is found that water pressure and traverse speed are most significant process parameters influencing kerf taper angle. Based on the analysis, a predictive model is developed to predict kerf taper angle. The confirmation tests are performed to verify the predicative model. The findings of present work is useful in minimizing the kerf taper during AWJM of composite materials.